Affinity Purification of an Archaeal DNA Replication Protein Network - Li, Zhuo (American Society of Microbiology, 2010)
Nineteen Thermococcus kodakarensis strains have been constructed, each of which synthesizes a different His(6)-tagged protein known or predicted to be a component of the archaeal DNA replication machinery. Using the His(6)-tagged proteins, stable complexes assembled in vivo have been isolated directly from clarified cell lysates and the T. kodakarensis proteins present have been identified by mass spectrometry. Based on the results obtained, a network of interactions among the archaeal replication proteins has been established that confirms previously documented and predicted interactions, provides experimental evidence for previously unrecognized interactions between proteins with known functions and with unknown functions, and establishes a firm experimental foundation for archaeal replication research. The proteins identified and their participation in archaeal DNA replication are discussed and related to their bacterial and eukaryotic counterparts.